2019
DOI: 10.1007/s11664-019-07460-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Au Addition on the Crystallinity and Electrical Properties of Thermally Strained LaNiO3−δ Thin Films

Abstract: We prepared Au-LaNiO 3Àd (Au-LNO) nanocomposite thin films by a sol-gel coating method. The effects of the doped Au on the microstructure and electrical properties of the Au-LNO films under different types of thermal strain were investigated. Introduction of Au into the LNO films changed their preferential orientation and markedly lowered their room-temperature resistivity. Moreover, the resistivity of the films containing Au nanoparticles showed negligible dependence on thermal strain, in contrast to the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To explain this phenomenon, we have also prepared pure LaNiO 3−δ NFs via a similar procedure without the addition of Au precursor. It is found that the XRD lattice of the fiber is a perfect LaNiO 3 phase (inset figure in Figure f), that is, the addition of HAuCl 4 yields a variety of different types of oxides . After seven days of Hac-NaAc acidification, the lattice of A-Au/LaNiO 3−δ NFs is restructured, that is, the LaNiO 3 lattice increases, and some other oxide lattices disappear.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To explain this phenomenon, we have also prepared pure LaNiO 3−δ NFs via a similar procedure without the addition of Au precursor. It is found that the XRD lattice of the fiber is a perfect LaNiO 3 phase (inset figure in Figure f), that is, the addition of HAuCl 4 yields a variety of different types of oxides . After seven days of Hac-NaAc acidification, the lattice of A-Au/LaNiO 3−δ NFs is restructured, that is, the LaNiO 3 lattice increases, and some other oxide lattices disappear.…”
Section: Resultsmentioning
confidence: 98%
“…However, the XRD peaks of LaNiO 3−δ are more complex, which include a series of different crystal planes of the derivatives of LaNiO 1f), that is, the addition of HAuCl 4 yields a variety of different types of oxides. 28 After seven days of Hac-NaAc acidification, the lattice of A-Au/LaNiO 3−δ NFs is restructured, that is, the LaNiO 3 lattice increases, and some other oxide lattices disappear.…”
Section: ■ Results and Discussionmentioning
confidence: 99%